Termohidravlične varnostne analize v podporo zamenjavi uparjalnikov in povečanju moči v jedrski elektrarni Krško - Mavko, Borut (Strojniški vestnik, 2000)
The Krško nuclear power plant has undertaken a major modernization project. The objectives of the project are: long-term stabilization of the plant's operation, uprating of the net electrical power output, higher availability and enhanced safety of the plant. The modernization also requires a thorough safety re-avaluation and therefore new thermal hydraulic, mechanical and structural analysis. The thermal-hydraulic part of the safety analysis necessary for the steam generator replacement and the power uprating were performed and independently reviewed according to Slovenian and USNRC (United states nuclear regulatory commission) requirements. The analysis and the review focused on the plant conditions assumed to be the most-critical for the operating window. The limiting transient and accident cases were identified and described in an updated safety analysis report. Results of the safety analysis and independent safety review indicate that the objectives of the Krško modernization project can be met and will contribute to the plant's safe and reliable long-term operation.
Keywords: varnost jedrska; analize varnosti; kriteriji varnosti; modeli za vrednotenje; Nuklearna elektrarna Krško; modernizacija; security; varnost